The Outcome of Agitation in Poisoned Patients in an Iranian Tertiary Care University Hospital. (3rd December 2014) - Sabzghabaee, Ali Mohammad; Yaraghi, Ahmad; Khalilidehkordi, Elham; Mirhosseini, Seyyed Mohammad Mahdy; Beheshtian, Elham; Eizadi-Mood, Nastaran
Abstract : Introduction . This study was conducted to evaluate and document the frequency and causes of agitation, the symptoms accompanying this condition in intoxications, relationship between agitation score on admission and different variables, and the outcome of therapy in a tertiary care referral poisoning center in Iran. Methods . In this prospective observational study which was done in 2012, 3010 patients were screened for agitation at the time of admission using the Richmond Agitation Sedation Scale. Demographic data including age, gender, and the drug ingested were also recorded. The patients' outcome was categorized as recovery without complications, recovery with complications (hyperthermia, renal failure, and other causes), and death. Results . Agitation was observed in 56 patients (males, n = 41 ), mostly aged 19–40 years (n = 38 ) and more frequently in illegal substance (stimulants, opioids and also alcohol) abusers. Agitation score was not significantly related to the age, gender, and previous history of psychiatric disorders. Forty nine patients had recovery without any complication. The need for mechanical ventilation was the most frequent complication. None of the patients died. Conclusion . Drug abuse seems to be a must-to-consider etiology for patients presenting with acute agitation and its morbidity and mortality could be low in agitated poisoning cases if prompt supportive care is performed.